CONCEPTS OF LOYALTY AND BETRAYAL IN AMERICAN AND UZBEK CULTURES (TAMADDUN NURI JURNALI, 2025)
This article explores the concepts of loyalty and betrayal as complex moral and spiritual phenomena in human life. It examines how these themes are portrayed in literary works, where loyalty serves as a motivating force and betrayal as a source of emotional pain, thus shaping the universal pathos of the novel. The author successfully reveals the nation’s moral and spiritual development through the depiction of characters that embody qualities such as courage, resilience, humanism, patience, loyalty, and betrayal.